2021
DOI: 10.1212/nxi.0000000000000974
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Prognostic Value of Immunogenetic Characteristics in Anti-LGI1 Encephalitis

Abstract: ObjectiveAntibodies against leucine-rich glioma-inactivated 1 (LGI1-Abs) characterize a limbic encephalitis (LE) strongly associated with HLA-DRB1*07:01, although some patients lack LGI1-Abs in CSF or do not carry this allele. Whether they represent a different subtype of disease or have different prognoses is unclear.MethodsRetrospective analysis of clinical features, IgG isotypes, and outcome according to LGI1-Ab CSF positivity and DRB1*07:01 in a cohort of anti-LGI1 LE patients.ResultsPatients with LGI1-Abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
52
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 40 publications
7
52
1
Order By: Relevance
“…However, our patients had a relatively lower detection rate of LGI1 antibodies in CSF and better functional outcome compared to some other studies (2-4). Consistent with our findings, positive LGI1 antibodies in CSF were found to correlate with increased neuronal excitability (11) and poor outcome recently (8). Similarly, an elevated LGI1-IgG CSF index was reported to predict unfavorable neurological outcome (7), indicating that intrathecal antibody synthesis may lead to more severe neuronal impairment.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…However, our patients had a relatively lower detection rate of LGI1 antibodies in CSF and better functional outcome compared to some other studies (2-4). Consistent with our findings, positive LGI1 antibodies in CSF were found to correlate with increased neuronal excitability (11) and poor outcome recently (8). Similarly, an elevated LGI1-IgG CSF index was reported to predict unfavorable neurological outcome (7), indicating that intrathecal antibody synthesis may lead to more severe neuronal impairment.…”
Section: Discussionsupporting
confidence: 88%
“…Consistent with previous studies (2-5), our patients showed typical manifestations such as seizures (particularly FBDS) and cognitive deficit, and some patients had hippocampal T2/FLAIR hyperintense signals or hippocampal atrophy/sclerosis. This is because LGI1 antibodies [mainly of IgG4 subclass (2,7,8)] are believed to alter K v 1.1 subunit of VGKC as well as AMPA receptors, causing neuronal hyperexcitability and reducing longterm synaptic plasticity in the hippocampus (1,9). HLA class II was reported to relate with anti-LGI1 encephalitis, particularly HLA-DRB1*07:01 (8,10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…What matters in the context of the topic under discussion in autoimmune diseases of the central and peripheral nervous system with importance of CASPR2, CASPR1, LGI1, or neurofascin 155 antibodies is that the shared feature is the predominance of antigen-specific antibodies of the IgG4 subclass ( 30 , 31 ).…”
Section: Igg4 Autoimmune-related Diseasesmentioning
confidence: 99%
“…The heterogeneity of the environmental factors described in anti-NMDAR encephalitis could potentially interplay with an eventual genetic predisposition. The human leukocyte antigen (HLA) is the main genetic factor related to autoimmunity, with several associations in neurological diseases driven by neural antibodies [ 90 ], being especially strong between DRB1*07:01 and limbic encephalitis (LE) with antibodies against leucine-rich glioma inactivated 1 [ 91 , 92 , 93 , 94 ] and between DRB1*11:01 and LE with antibodies against contactin-associated protein-like 2 (CASPR2) [ 93 , 95 ]. On the contrary, a first study including a small cohort of patients with anti-NMDAR encephalitis found no association with HLA [ 91 ].…”
Section: Molecular Biomarkers In Anti-nmdar Encephalitismentioning
confidence: 99%